A Novel Recyclable Strategy for Extraction of Naproxen Sodium from Environmental Water by Amino-Functionalized Immobilized Ionic Liquid Polymers - Hongrui Yang; Ayiguli Maimaiti; Wei Liu; Wenye Deng; Xiaoping Fu; Jing Fan (Molecules)
Naproxen sodium is an emerging pollutant that may pose potential hazards to human health and the ecological environment. However, developing highly effective adsorbents for the extraction of naproxen sodium from aqueous environments is still a challenge. Herein, we have prepared a novel amino-functional ionic liquid polymer adsorbent (NH2-IL-PS) for the extraction of naproxen sodium (NPS) from aqueous environments. It was found that the NH2-IL-PS exhibits a high adsorption capacity of 456.6 mg/g for NPS and maintains high extraction efficiency over a wide pH range of 4 to 9 at room temperature. Notably, even when the concentration of NPS was lower than 5 ppb, the extraction efficiency still exceeded 90.0%, with the enrichment factor reaching up to 600.0. More importantly, the NH2-IL-PS adsorbent material can withstand at least 16 consecutive adsorption cycles while maintaining an extraction efficiency of over 90.0%. Finally, the NH2-IL-PS was successfully applied to extract and determine NPS in seven types of real water samples, with relative recoveries ranging from 90.9 to 96.2%. The study of the adsorption mechanism reveals that electrostatic interactions, ion exchange, π-π stacking, and hydrogen bonding are crucial in the extraction of NPS. This study provides a sustainable strategy for the efficient extraction of NPS.